Self-Regulated Learning (SRL) Tendencies of Educational Technology Students in Online Tutorials - Syarif, Edy; Prastati, Trini; Abd Gafur; Asnah Marlina Limbong (LPPM Universitas Terbuka, 2025)
This study examines the tendency of Self-Regulated Learning (SRL) among Educational Technology students at Universitas Terbuka (UT) in participating in online tutorials (tuton). SRL reflects students’ ability to independently manage, control, and monitor their own learning, which is essential in online learning environments. The survey involved 249 respondents (36% of the sample) from various UT regional offices, using the SRL instrument developed by Riyanti (2021), which measures six aspects: Goal Setting, Environment Structuring, Task Strategies, Time Management, Help Seeking, and Self-Evaluation. The results show the highest score in Goal Setting (87.94%) and the lowest in Time Management (50.68%). These findings indicate that students' SRL abilities are not yet evenly developed, highlighting the need for more structured and independent learning strategies in online education